Efek Pelatihan Pemahaman Emosi Pada Anak Retardasi Mental Ringan di SLBN Pembina Yogyakarta - Mentari Marwa (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2018)
Mild mental retardation. The method used to practice understanding the log using log cards. The child is asked to hold the emotion card correctly, answer the emotion that is being shown by the character on the emotional card, demonstrating the emotions everyday, then identifying an event or situation based on emotion. This study used a quasi experimental design with two subjects who had been diagnosed with mild mental retardation. The results obtained were that emotional understanding training had an effect in increasing emotional understanding in the first subject but did not have an effect on understanding emotions in the second subject.